Begonia ciliatifolia (Begoniaceae), a rare, critically endangered new species endemic from Santa Catarina, southern Brazil - Funez, Luís Adriano; Jaramillo, Julio Cesar (Phytotaxa, 2019)
We describe here Begonia ciliatifolia, a new species from Santa Catarina, southern Brazil. We treat the species as a member of Begonia sect. Pritzelia, and discuss its differences to related species. Due the species small area of occurrence and the very specific habitat, the new species is assessed as critically endangered according to IUCN criteria. Additionally, we present a distribution map, field photographs and a key to the species of Begonia with peltate leaves and corniculate fruits of South Region of Brazil.